2021
DOI: 10.1089/aut.2020.0063
|View full text |Cite
|
Sign up to set email alerts
|

“People Might Understand Me Better”: Diagnostic Disclosure Experiences of Autistic Individuals in the Workplace

Abstract: Background: Autistic individuals face challenges in the workplace, particularly related to social communication. Diagnostic disclosure may mitigate these challenges, but it also exposes individuals to potential discrimination. This study aimed to share the diagnostic disclosure experiences of autistic adults in the workplace to help employers better understand the process, and help other autistic individuals make an informed decision about disclosure. Methods: The participants in this study were 238 clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 37 publications
5
52
1
Order By: Relevance
“…The mixed outcomes of disclosure determined by past research (Lindsay et al, 2019;Romualdez et al, 2020) were also confirmed by the current study. These included negative outcomes (i.e., problematic stereotyping, active discrimination, and disadvantages in recruitment) as well as positive ones: improved mental health and well-being, acceptance and support from others, and positive organisational changes.…”
Section: Discussionsupporting
confidence: 81%
“…The mixed outcomes of disclosure determined by past research (Lindsay et al, 2019;Romualdez et al, 2020) were also confirmed by the current study. These included negative outcomes (i.e., problematic stereotyping, active discrimination, and disadvantages in recruitment) as well as positive ones: improved mental health and well-being, acceptance and support from others, and positive organisational changes.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, many participants felt unable to request adjustments without disclosing a formal autism diagnosis. This finding is consistent with recent findings by Romualdez et al [19], who found that disclosure was perceived as a necessity by autistic employees, as opposed to a choice (see also, [11]). However, the requirement to provide information about one's diagnosis in order to gain access to necessary workplace adjustments is problematic for several reasons.…”
Section: Plos Onesupporting
confidence: 93%
“…This not only resulted in high levels of distress for those participants, or in their departure from certain settings, but reinforced a fear of sharing their diagnosis. Uncertainties over revealing diagnosis are similarly reported in studies focussed on teachers with LD (Valle et al 2004;Vogel and Sharoni 2011), teachers and trainee teachers who are dyslexic (Riddick 2003) and on the employment of autistic people in the UK (Martin, Barnham, and Krupa 2019;Vincent 2020;Romualdez et al 2021). For the participants in this study, being unable to share the fact of being autistic could result in 'masking' or 'camouflaging' autistic traits, a process found to be stressful, exhausting and to have a negative impact on self-esteem (Lai et al 2017;Cassidy et al 2020).…”
Section: Discussionmentioning
confidence: 87%